Aluminium porphyrins catalyse the hydrogenation of CO 2 with H 2 - Kumar, Nitin (2024)
Boron-based frustrated Lewis pairs (FLPs) have become well-established catalysts for the hydrogenation of a wide range of functional groups. Conversely, aluminium-based FLP hydrogenation catalysts are less common, especially for CO2 reduction. They are mostly confined to the hydrogenation of imines, alkenes, and alkynes even though aluminium is much more abundant than boron and forms structurally related compounds. Moreover, aluminium forms penta- and hexa-coordinated complexes, which remain untested in FLP hydrogenation catalysis. Herein, we demonstrate that cationic, hexa-coordinated diaqua-meso-tetraphenylporphyrin aluminium complexes [Al(TPP)(OH2)2]X and [Al(t BuTPP)(OH2)2]X (X = Cl−, OTf−, ClO4 −) form FLPs with nitrogen bases, activate H2, and reductively couple CO2 to amines, yielding N-formylamines and water. Our experimental results and DFT analysis indicate that H2 activation involves the formation of an FLP, base-promoted CO2 reduction and formate salt elimination from the FLP, as proposed for transition metal-catalyzed N-formylations. These similarities in the reaction mechanism and structure of aluminium complexes brings Al-based FLPs closer to transition metal catalysis and may enable us to apply this knowledge to ligand design to enhance main group metalpromoted hydrogenations.